Erythrogram Profile of Blood Samples Anticoagulated with Tri-potassium Ethylene Diamine Tetraacetic Acid (K3EDTA) Stored for 48 Hours at 4oC - Azzahrah, Putri; Esfandiari, Anita; Mihardi, Arief Purwo; Widhyari, Sus Derthi; Wulansari, Retno; Ningtias, Putri Indah (Jurnal Medik Veteriner, 2024)
Several pre-analytical variables influence hematological results, including anticoagulant use, storage temperature, and time between blood sample collection and analysis. Delayed sample analysis owing to prolonged storage could result in erythrogram profiles, which could complicate the interpretation of the resulting data. This study investigated the erythrogram profile of tripotassium ethylenediaminetetraacetic acid (K3EDTA) in blood samples stored for 48 h at 4°C. Ten healthy blood samples of Ongole crossbred cattle were collected into K3EDTA tubes from the jugular or coccygeal veins and analyzed for erythrogram profiles (erythrocyte counts, hemoglobin levels, hematocrit value, and erythrocyte morphology). Blood sample analysis for the control (0 h) was performed within ± 1.5 hours after collection, then the samples were refrigerated (4°C) and analyzed at 3, 6, 9, 12, 24, and 48 h. The results showed increased (p < 0.05) erythrocyte counts and hematocrit values after 9–24 and 6–48 h of storage, respectively. There was a significant difference in erythrocyte diameter between 0 h and other time observations (p < 0.05). Echinocytes were observed at 0 h of storage and continued to increase up to 48 h. Hypochromasia was also found at 6 to 48 hours of storage. Therefore, the analysis of blood samples for erythrogram parameters should be performed as soon as possible, preferably within three hours after collection, to ensure clinically reliable results.